Studi Nilai Karakter pada Simbolisme Batik Ngawi Motif Srambang Park dalam Pembelajaran Seni Rupa - Tri Hartatik; Retno Winarni; Anesa Surya (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aimed to describe the character values in the symbolism of Ngawi Batik Srambang Park motif in art learning based on cultural diversity in elementary schools. This research used a qualitative descriptive method with a hermeneutic approach. The subjects of this study were three Ngawi Batik craftsmen. The data collection technique was done by observing, interviewing and documenting. The data analysis technique used the Miles and Huberman model data analysis technique with 4 stages including data collection, data reduction, data presentation, and conclusion drawing. The result of the research showed that there are values of religious character, hard work, peace-loving, friendly (communicative), environmental care, social care, responsibility, respect for achievement, love for the country, and independence in the symbolism of Ngawi Batik for Srambang Park motif. The use of Batik Srambang Park motif for learning in elementary schools had two relevance. First, character education values were reflected in Batik Srambang Park. Second, Srambang Park Batik was a two-dimensional regional art work. Thus, the learning is not only teaching about the concept of understanding the material but also teaching character values.